2001
DOI: 10.1149/1.1379031
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Phase Control of Dy Alloy Films by Electrochemical Implantation and Displantation

Abstract: The electrochemical formation of Dy-Ni alloys was studied in a molten normalLiCl­normalKCl­DyCl3 (0.50 mol %) system at 700 K. Potentiostatic electrolysis of a Ni electrode at 0.55 (vs. Li+/normalLifalse), 0.62, and 0.70 V for 2 h resulted in formations of the coherent and minute DyNi2 films having thickness of about 60, 30, and 20 μm, respectively. The growth rates of the DyNi2 films were extremely high, when considering conventional solid phase diffusion. Moreover, the growth rate was dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 14 publications
6
85
2
Order By: Relevance
“…2), suggesting that some formation process are relatively slow [13] and lithium atoms diffuse with low rates in the solid solution. This voltammetric results are similar to those for the Dy-Ni and Pr-Ni system [12,13]. …”
Section: Cyclic Voltammetrysupporting
confidence: 85%
See 1 more Smart Citation
“…2), suggesting that some formation process are relatively slow [13] and lithium atoms diffuse with low rates in the solid solution. This voltammetric results are similar to those for the Dy-Ni and Pr-Ni system [12,13]. …”
Section: Cyclic Voltammetrysupporting
confidence: 85%
“…Castrillejo et al [6][7][8][9][10] studied electrochemical behavior of Dy, Er, Gd, Pr and Ho on Al electrode in the eutectic LiCl-KCl, and produced corresponding Al-based alloys. Nohira and co-workers [11][12][13] investigated electrochemical formation and phase control of Sm-Ni, Dy-Ni and Pr-Ni alloys on Ni electrode. Smolinski et al [14,15] studied the preparation process of Mg-Li by electrolysis in molten salts in the temperature range of 773-903 K. Our group has first prepared different contents Mg-Li alloys via a twoelectrode cell in a molten salt electrolyte (50 wt.% LiCl-50 wt.% KCl) at 693-783 K. The optimal temperature was 753 K, which corresponds to the highest current efficiency [16].…”
Section: Introductionmentioning
confidence: 99%
“…10 Although the deposition/ dissolution potentials of Nd and Dy are barely different from each other, there is a significant difference in the formation/dissolution potentials of Nd-Ni and Dy-Ni alloys. For example, Dy is cathodically deposited to form Dy-Ni alloy on the Ni substrate cathode (electrochemical implantation) according to the following reaction:…”
Section: Electrochemistry 86(2) 21-28 (2018)mentioning
confidence: 99%
“…Also, there are six potential plateaus due to the dissociation of Nd in the Cd film into the salt, and the potential increases in the positive direction and the plateaus are formed sequentially. Many researchers have reported that this potential plateau in the CP experiment means is a two-phase region [21,33,[41][42][43][44]. According to the studies, when the compounds of the two different compositions coexist on the surface of the electrode, the activity of the metal element is maintained constant by the equilibrium until one compound completely changes to another compound, and thus, the electro motive force (EMF) remains constant [42].…”
Section: Electrochemical Reaction Of Ndcl 3 In Licl-kcl At Cd-coated mentioning
confidence: 99%